Navigating urban ecology: Conceptual and methodological insights - Ian MacGregor‐Fors; Christine C. Rega‐Brodsky; D. Johan Kotze; J. Scott MacIvor; Amy K. Hahs; Marco Moretti; Nicholas S. G. Williams; Christopher A. Lepczyk; Kirsten Jung; Madhusudan Katti; Sonja Knapp; Frank A. La Sorte; et al. (Ecology, 2026)
Since its consolidation as a sub‐discipline of ecology in the late 1990s, urban ecology has grown substantially, enhancing our understanding of how urbanization shapes biodiversity and how biodiversity adapts to urbanization. Inherently interdisciplinary in its scope and application, urban ecology is rooted in multiple theoretical and methodological foundations, potentially making the field overwhelming for newcomers as the key literature is scattered across multiple disciplines. Drawing on the collective expertise of editors and reviewers, we attempt to address common pitfalls noted in studies of biodiversity within urban ecosystems and suggest action items for both the new and experienced urban ecologist. Here, we present key concepts for framing hypothesis‐based urban biodiversity research questions, conceptualizing urban settings, accounting for spatial and temporal scales, selecting study systems and meaningful explanatory variables for research questions, and recognizing the social‐ecological nature of urban systems. We offer insights and examples, emphasizing the importance of rigorous urban ecological research without imposing constraints on innovation.

Riparian Forests and Macroinvertebrates Support Multiple Ecosystem Processes Across Temperate and Tropical Streams - Rebecca Oester; Paula M. de Omena; Larissa Corteletti da Costa; Marcelo S. Moretti; Florian Altermatt; Andreas Bruder (Ecosystems, 2026)
Ecosystems are interconnected, and ecological processes frequently transcend the physical boundaries that define them. Fluxes of energy, matter, and organisms not only form important ecosystem processes within but also between ecosystems. However, the role of biological drivers in simultaneously supporting multiple ecosystem processes at the interface between aquatic and terrestrial ecosystems (that is, aquatic-terrestrial ecosystem processes) remains poorly understood, both locally and across regions. To assess the relative importance of riparian forests, detritus consumers and leaf litter mixing on different ecosystem processes of freshwater detrital food webs, we used leaf litter bags to subsidise local terrestrial leaf litter to forested and non-forested headwater stream sites in a temperate and tropical region. We also manipulated macroinvertebrate access and the composition of leaf litter mixtures. We measured three key aquatic-terrestrial ecosystem processes: biomass accrual of aquatic fungi, nitrogen loss, and decomposition rates of local leaf litter. Across both temperate and tropical streams, ecosystem multifunctionality, that is, the simultaneous sustaining of these processes, was positively associated with macroinvertebrates and riparian forests but not with leaf litter mixing. Especially leaf litter nitrogen loss and decomposition rates were consistently higher when macroinvertebrates had access across all leaf litter species. Decomposition rates were also positively associated with the other ecosystem processes. These findings highlight consistent, cross-regional effects of riparian forests and macroinvertebrate detritivores on freshwater detrital food webs. In a rapidly changing world, understanding ecosystem processes in headwater streams demands a holistic view that transcends ecosystem borders and incorporates cross-ecosystem interactions.

Global-scale AI-powered prediction of hydrogen seeps - V. Roche; J. Daynac; S. Hesni; U. Geymond; N. Ginzburg; J. Philippon; I. Moretti (Marine and Petroleum Geology, 2026)

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

The global role of bioassessment in policy delivery and decision-making for inland waters - Martyn G. Kelly; Gary Free; John P. Simaika; Stuart Warner; Andreas Bruder; Alejandra Correa-Bedoya; Fabio de Oliveira Roque; Tor Erik Eriksen; Jennifer Lento; Craig R. Macadam; Kristian Meissner; Marcelo S. Moretti; et al. (Journal of Environmental Management, 2025)

Mössbauer spectroscopy: a key tool to quantify Fe-speciation and distribution in H2-generating rocks - U. Geymond; K. Loiseau; V. Roche; G. Pasquet; S. Revillon; M. Sougrati; I. Moretti (Applied Geochemistry, 2025)

A Global Synthesis on Land‐Cover Changes in Watersheds Shaping Freshwater Detrital Food Webs - Rebecca Oester; François Keck; Marcelo S. Moretti; Florian Altermatt; Andreas Bruder; Verónica Ferreira (Global Change Biology, 2025)
Anthropogenic land‐cover changes are among the most pressing global threats to both aquatic and terrestrial ecosystems, jeopardizing biodiversity and the critical connections between these systems. Resource flows and trophic interactions intricately link aquatic and terrestrial ecosystems, with terrestrial‐derived detritus playing a fundamental role in supporting aquatic food webs. These detrital inputs form essential cross‐ecosystem linkages, underpinning key ecological processes and providing vital resources for aquatic communities. Yet, little research has focused on how land‐cover changes cascade across this linkage. To better understand how land‐cover changes in the watershed influence freshwater detrital food webs, we conducted a meta‐analysis of field studies reporting the effects of vegetation changes on freshwater detrital consumers and organic matter decomposition. The results from 144 studies, reporting 1235 comparisons, showed that, overall, land‐cover changes in the watershed vegetation, especially through harvest and land‐use conversion, have negative effects on aquatic biodiversity and ecosystem processes. These vegetation changes reduced diversity, abundance, and biomass across multiple trophic levels in freshwater detrital food webs. Studies examining multiple organism groups most often observed negative responses across multiple trophic levels, suggesting that these land‐cover changes negatively affected multiple detrital food‐web components simultaneously. Our results also show that outcomes of restoration of watershed vegetation were context‐dependent, and no clear trend of improvement was visible. Therefore, conservation of natural riparian and catchment vegetation is key to maintaining freshwater ecosystem processes and aquatic biodiversity worldwide, and more efficient and evidence‐based restoration measures are urgently needed. As our global synthesis shows that direct human‐induced alterations of vegetation in watersheds have significant negative effects on freshwater detrital food webs, there is a pressing need to consider cross‐ecosystem consequences of land‐cover changes in conservation and ecosystem management.

Disruption of serotonin homeostasis in intestinal organoids provides insights into drug-induced gastrointestinal toxicity - Georgia M. Rouseti; Audrey Fischer; Nicole Rathfelder; Karen Grimes; Annick Waldt; Rachel Cuttat; Sven Schuierer; Sophia Wild; Magali Jivkov; Valerie Dubost; Heiko S. Schadt; Alex Odermatt; et al. (Toxicology, 2025)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Towards harmonized standards for freshwater biodiversity monitoring and biological assessment using benthic macroinvertebrates - John P. Simaika; James Stribling; Jennifer Lento; Andreas Bruder; Sandra Poikane; Marcelo S. Moretti; Nick Rivers-Moore; Kristian Meissner; Craig R. Macadam (Science of The Total Environment, 2024)

Floral species evenness is the major driver of wild bee communities in urban gardens - B.A. Rossi Rotondi; J. Casanelles-Abella; S. Fontana; M. Moretti; M. Videla; M.S. Fenoglio (Urban Ecosystems, 2024)

Allele and genotype frequencies for primary hereditary cataract, multifocal retinopathy 1, and degenerative myelopathy in Pyrenean Mountain dog from Italy - R. Moretti; G. Massimello; S. Chessa; S. Sartore; A. Tranchero; M. Profiti; P. Sacchi (Topics in Companion Animal Medicine, 2024)

How do macroconsumers interact with insect shredders in streams? A laboratory test using shrimp and caddisfly larvae that build cases with different organic materials - Pâmela Barbosa; Walace P. Kiffer; Larissa C. Costa; Flávio Mendes; Marcelo S. Moretti (Limnologica, 2023)

Hepatocellular carcinoma induced by hepatocyte Pten deletion reduces BAT UCP-1 and thermogenic capacity in mice, despite increasing serum FGF-21 and iWAT browning - Álbert S. Peixoto; Mayara F. Moreno; Érique Castro; Luiz A. Perandini; Thiago Belchior; Tiago E. Oliveira; Thayna S. Vieira; Gustavo R. Gilio; Caroline A. Tomazelli; Bianca F. Leonardi; Milene Ortiz-Silva; Luciano P. Silva Junior; et al. (Journal of Physiology and Biochemistry, 2023)

Leaf-associated macroinvertebrate assemblage and leaf litter breakdown in headwater streams depend on local riparian vegetation - Rebecca Oester; Paula C. dos Reis Oliveira; Marcelo S. Moretti; Florian Altermatt; Andreas Bruder (Hydrobiologia, 2023)
Headwater streams harbor diverse macroinvertebrate communities and are hotspots for leaf litter breakdown. The process of leaf litter breakdown mediated by macroinvertebrates forms an important link between terrestrial and aquatic ecosystems. Yet, how the vegetation type in the local riparian zone influences leaf-associated macroinvertebrate assemblages and leaf litter breakdown rates is still not resolved. We investigated how leaf-associated macroinvertebrate assemblages and leaf litter fragmentation rates differ between forested and non-forested sites using experimental leaf litter bags in sixteen sites paired across eight headwater streams in Switzerland. Our results show that sensitive taxa of the invertebrate orders Ephemeroptera, Plecoptera and Trichoptera (EPT) and the functional group of shredders were strongly associated with forested sites with overall higher values of abundance, diversity, and biomass of EPTs in forested compared to non-forested sites. However, the importance of riparian vegetation differed between study regions, especially for shredders. Fragmentation rates, which are primarily the result of macroinvertebrate shredding, were on average three times higher in forested compared to non-forested sites. Our results demonstrate that not only the composition of the aquatic fauna but also the functioning of an essential ecosystem process depend on the vegetation type in the local riparian zone.

Ecosystem services provided by small streams: an overview - Verónica Ferreira; Ricardo Albariño; Aitor Larrañaga; Carri J. LeRoy; Frank O. Masese; Marcelo S. Moretti (Hydrobiologia, 2023)

Diverse magma storage and major and volatile magma composition: What are the implications on the eruptive style across a volcanic arc? An example of the Lesser Antilles Arc - A. Metcalfe; S. Moune; J.-C. Komorowski; R. Robertson; T.E. Christopher; E.P. Joseph; R. Moretti (Earth-Science Reviews, 2023)

Sex-dependent modulation of caerulein-induced acute pancreatitis in C57BL/6J mice: histopathological and immunohistochemical characterization - L. Bertola; G. Pepe; A. Dolce; A. Cappelleri; S. Canesi; P. Moretti; A. Giordano; E. Scanziani; E. Vegeto; C. Recordati (Journal of Comparative Pathology, 2023)

An overview of microplastic research in marine and freshwater habitats using topic modeling - Jamine D. Rezende; Marcelo S. Moretti (Hydrobiologia, 2023)

Sedimentological features of asbestos cement fragments in coastal environments (Taranto, southern Italy) - S. Lisco; I. Lapietra; R. Laviano; G. Mastronuzzi; T. Fracchiolla; M. Moretti (Marine Pollution Bulletin, 2023)

Experimental assessment of an indirect method to measure the post-combustion flue gas flow rate in waste-to-energy plant based on multi-point measurements - G. Bellani; L. Lazzarini; A. Dal Pozzo; S. Moretti; M. Zattini; V. Cozzani; A. Talamelli (Waste Management, 2023)

Quantifying the response of Blainville's beaked whales to U.S. naval sonar exercises in Hawaii - Eiren K. Jacobson; E. Elizabeth Henderson; David L. Miller; Cornelia S. Oedekoven; David J. Moretti; Len Thomas (Marine Mammal Science, 2022)
Behavioral responses of beaked whales (family Ziphiidae) to naval use of mid‐frequency active sonar (MFAS) have been quantified for some species and regions. We describe the effects of MFAS on the probability of detecting diving groups of Blainville's beaked whales on the U.S. Navy Pacific Missile Range Facility (PMRF) in Hawaii and compare our results to previously published results for the same species at the Atlantic Undersea Test and Evaluation Center (AUTEC) in the Bahamas. We use passive acoustic data collected at bottom‐mounted hydrophones before and during six naval training exercises at PMRF along with modelled sonar received levels to describe the effect of training and MFAS on foraging groups of Blainville's beaked whales. We use a multistage generalized additive modeling approach to control for the underlying spatial distribution of vocalizations under baseline conditions. At an MFAS received level of 150 dB re 1 μPa rms the probability of detecting groups of Blainville's beaked whales decreases by 77%, 95% CI [67%, 84%] compared to periods when general training activity was ongoing and by 87%, 95% CI [81%, 91%] compared to baseline conditions. Our results indicate a more pronounced response to naval training and MFAS than has been previously reported.

Urban biodiversity: State of the science and future directions - Christine C. Rega-Brodsky; Myla F. J. Aronson; Max R. Piana; Ela-Sita Carpenter; Amy K. Hahs; Adriana Herrera-Montes; Sonja Knapp; D. Johan Kotze; Christopher A. Lepczyk; Marco Moretti; Allyson B. Salisbury; Nicholas S. G. Williams; et al. (Urban Ecosystems, 2022)

Involvement of serotonergic neurotransmission in the antidepressant-like effect elicited by cholecalciferol in the chronic unpredictable stress model in mice - Vivian B. Neis; Isabel Werle; Morgana Moretti; Priscila B. Rosa; Anderson Camargo; Yasmim de O. Dalsenter; Nicolle Platt; Axel F. Rosado; William D. Engel; Gudrian Ricardo L. de Almeida; Ingrid Selhorst; Alcir Luiz Dafre; et al. (Metabolic Brain Disease, 2022)

Morpho-sedimentary dynamics of Torre Guaceto beach (Southern Adriatic Sea, Italy) - I Lapietra; S Lisco; G Mastronuzzi; S Milli; C Pierri; F Sabatier; G Scardino; M Moretti (Journal of Earth System Science, 2022)

Antidepressant-like effect of guanosine involves activation of AMPA receptor and BDNF/TrkB signaling - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Fernanda N. Kaufmann; Mauren K. Tavares; Isabel Werle; Yasmim Dalsenter; Nicolle Platt; Axel F. Rosado; Daiane B. Fraga; Isabella A. Heinrich; et al. (Purinergic Signalling, 2021)

Abundance, survival, and annual rate of change of Cuvier's beaked whales ( Ziphius cavirostris ) on a Navy sonar range - K. Alexandra Curtis; Erin A. Falcone; Gregory S. Schorr; Jeffrey E. Moore; David J. Moretti; Jay Barlow; Erin Keene (Marine Mammal Science, 2021)
Bayesian mark‐recapture estimates of survival, abundance, and trend are reported for Cuvier's beaked whales ( Ziphius cavirostris ) using a Navy training range off southern California. The deep‐diving beaked whale family is exceptionally vulnerable to mid‐frequency active sonar (MFAS), which has been implicated in mass strandings and altered foraging behavior. Extremely low sighting probabilities impede studies of population‐level impacts of MFAS on beaked whales. The San Nicolas Basin hosts a Navy training range subject to frequent MFAS use and attracts high densities of Z. cavirostris . An 11‐year (2007–2018) photo‐identification program leveraged automated acoustic detection and location capabilities on the range's 1,800‐km 2 hydrophone array to enhance capture probability. Estimated population parameters for Z. cavirostris using the range included mean (90% credibility intervals) apparent annual survival of 0.950 (0.899–0.986), annual number of individuals as 121 (71–219), and annual rate of change of −0.8% (−5.6%–4.1%). Simulations show the probability of detecting abundance changes is currently low, but can be greatly improved through continued monitoring and increased effort. Complementary data collection on habitat use and demographic rates in San Nicolas and surrounding basins is also essential to relating direct effects of MFAS use to changes in vital rates and broader population outcomes.

The involvement of GABAergic system in the antidepressant-like effect of agmatine - Vivian Binder Neis; Axel Fogaça Rosado; Gislaine Olescowicz; Morgana Moretti; Priscila Batista Rosa; Nicole Platt; Ana Lúcia S. Rodrigues (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Lysine acetylation as drug target in fungi: an underexplored potential in Aspergillus spp. - Natália Sayuri Wassano; Ariely Barbosa Leite; Franqueline Reichert-Lima; Angelica Zaninelli Schreiber; Nilmar S. Moretti; André Damasio (Brazilian Journal of Microbiology, 2020)

A preliminary investigation of corpus callosum subregion white matter vulnerability and relation to chronic outcome in boxers - Ashley L. Ware; Elisabeth A. Wilde; Mary R. Newsome; Paolo Moretti; Tracy Abildskov; Gregory S. Vogt; Stephen R. McCauley; Gerri Hanten; Jill V. Hunter; Zili D. Chu; Harvey S. Levin (Brain Imaging and Behavior, 2020)

Niche breadth of invertebrate shredders in tropical forest streams: which taxa have restricted habitat preferences? - Karoline Victor Serpa; Walace Pandolpho Kiffer; Miliane Fardim Borelli; Marcos Antônio Ferraz; Marcelo S. Moretti (Hydrobiologia, 2020)

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

Effects of cholecalciferol on behavior and production of reactive oxygen species in female mice subjected to corticosterone-induced model of depression - Suene Vanessa da Silva Souza; Priscila Batista da Rosa; Vivian Binder Neis; Júlia Dubois Moreira; Ana Lúcia S. Rodrigues; Morgana Moretti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Behavioral responses of satellite tracked Blainville's beaked whales ( Mesoplodon densirostris ) to mid‐frequency active sonar - Trevor W. Joyce; John W. Durban; Diane E. Claridge; Charlotte A. Dunn; Leigh S. Hickmott; Holly Fearnbach; Karin Dolan; David Moretti (Marine Mammal Science, 2020)
The vulnerability of beaked whales (Family: Ziphiidae) to intense sound exposure has led to interest in their behavioral responses to mid‐frequency active sonar (MFAS, 3–8 kHz). Here we present satellite‐transmitting tag movement and dive behavior records from Blainville's beaked whales ( Mesoplodon densirostris ) tagged in advance of naval sonar exercises at the Atlantic Undersea Test and Evaluation Center (AUTEC) in the Bahamas. This represents one of the largest samples of beaked whales individually tracked during sonar operations ( n = 7). The majority of individuals (five of seven) were displaced 28–68 km after the onset of sonar exposure and returned to the AUTEC range 2–4 days after exercises ended. Modeled sound pressure received levels were available during the tracking of four individuals and three of those individuals showed declines from initial maxima of 145–172 dB re 1 μPa to maxima of 70–150 dB re 1 μPa following displacements. Dive behavior data from tags showed a continuation of deep diving activity consistent with foraging during MFAS exposure periods, but also suggested reductions in time spent on deep dives during initial exposure periods. These data provide new insights into behavioral responses to MFAS and have important implications for modeling the population consequences of disturbance.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The antidepressant-like effect of guanosine is dependent on GSK-3β inhibition and activation of MAPK/ERK and Nrf2/heme oxygenase-1 signaling pathways - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Isabel Werle; Rodrigo B. Leal; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2019)

The longer the conditioning, the better the quality? The effects of leaf conditioning time on aquatic hyphomycetes and performance of shredders in a tropical stream - Cinthia G. Casotti; Walace P. Kiffer; Larissa C. Costa; Pâmela Barbosa; Marcelo S. Moretti (Aquatic Ecology, 2019)

Infection incidence, kernel colonisation, and mycotoxin accumulation in durum wheat inoculated with Fusarium sporotrichioides, F. langsethiae or F. poae at different growth stages - L. Nazari; E. Pattori; S. Somma; V. Manstretta; C. Waalwijk; A. Moretti; G. Meca; V. Rossi (European Journal of Plant Pathology, 2019)

Multisource data integration to investigate one century of evolution for the Agnone landslide (Molise, southern Italy) - M. Del Soldato; A. Riquelme; S. Bianchini; R. Tomàs; D. Di Martire; P. De Vita; S. Moretti; D. Calcaterra (Landslides, 2018)

Biotic interactions in species distribution modelling: 10 questions to guide interpretation and avoid false conclusions - Carsten F. Dormann; Maria Bobrowski; D. Matthias Dehling; David J. Harris; Florian Hartig; Heike Lischke; Marco D. Moretti; Jörn Pagel; Stefan Pinkert; Matthias Schleuning; Susanne I. Schmidt; Christine S. Sheppard; et al. (Global Ecology and Biogeography, 2018)
Aim Recent studies increasingly use statistical methods to infer biotic interactions from co‐occurrence information at a large spatial scale. However, disentangling biotic interactions from other factors that can affect co‐occurrence patterns at the macroscale is a major challenge. Approach We present a set of questions that analysts and reviewers should ask to avoid erroneously attributing species association patterns to biotic interactions. Our questions relate to the appropriateness of data and models, the causality behind a correlative signal, and the problems associated with static data from dynamic systems. We summarize caveats reported by macroecological studies of biotic interactions and examine whether conclusions on the presence of biotic interactions are supported by the modelling approaches used. Findings Irrespective of the method used, studies that set out to test for biotic interactions find statistical associations in species’ co‐occurrences. Yet, when compared with our list of questions, few purported interpretations of such associations as biotic interactions hold up to scrutiny. This does not dismiss the presence or importance of biotic interactions, but it highlights the risk of too lenient interpretation of the data. Combining model results with information from experiments and functional traits that are relevant for the biotic interaction of interest might strengthen conclusions. Main conclusions Moving from species‐ to community‐level models, including biotic interactions among species, is of great importance for process‐based understanding and forecasting ecological responses. We hope that our questions will help to improve these models and facilitate the interpretation of their results. In essence, we conclude that ecologists have to recognize that a species association pattern in joint species distribution models will be driven not only by real biotic interactions, but also by shared habitat preferences, common migration history, phylogenetic history and shared response to missing environmental drivers, which specifically need to be discussed and, if possible, integrated into models.

Accessing Gene Expression in Treatment-Resistant Schizophrenia - Patricia N. Moretti; Vanessa K. Ota; Eduardo S. Gouvea; Mariana Pedrini; Marcos L. Santoro; Fernanda Talarico; Leticia M. Spindola; Carolina Muniz Carvalho; Cristiano Noto; Gabriela Xavier; Elisa Brietzke; Ary Gadelha; et al. (Molecular Neurobiology, 2018)

Evidence for the involvement of opioid system in the antidepressant-like effect of ascorbic acid - Morgana Moretti; Camille M. Ribeiro; Vivian B. Neis; Luis Eduardo B. Bettio; Priscila B. Rosa; Ana Lúcia S. Rodrigues (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Structural and functional composition of invertebrate communities associated with leaf patches in forest streams: a comparison between mesohabitats and catchments - Flávio Mendes; Walace P. Kiffer; Marcelo S. Moretti (Hydrobiologia, 2017)

Advanced interpretation of interferometric SAR data to detect, monitor and model ground subsidence: outcomes from the ESA-GMES Terrafirma project - F. Raspini; S. Bianchini; S. Moretti; C. Loupasakis; D. Rozos; J. Duro; M. Garcia (Natural Hazards, 2016)

Monitoring population‐level responses of marine mammals to human activities - Erica Fleishman; Daniel P. Costa; John Harwood; Scott Kraus; David Moretti; Leslie F. New; Robert S. Schick; Lisa K. Schwarz; Samantha E. Simmons; Len Thomas; Randall S. Wells (Marine Mammal Science, 2016)
We provide guidance for monitoring whether human activities affect the physiology or behavior of marine mammals and, if so, whether those effects may lead to changes in survival and reproduction at the population level. We suggest that four elements be included in designing and implementing such a monitoring program. The first is development of a theory of change: a set of mechanistic hypotheses that outline why a given activity might be expected to have one or more measurable effects on individuals and populations, and ideally the magnitude, timing, and duration of the effects. The second element, definition of biologically meaningful effect sizes, ultimately facilitates the development of a monitoring program that can detect those magnitudes of effect with the desired levels of precision. The third element, selection of response variables for monitoring, allows inference to whether observed changes in the status of individuals or populations are attributable to a given activity. Visual observations, passive acoustic and tagging instruments, and direct physical measurements all can provide data that facilitate quantitative hypothesis testing. The fourth element is specification of the temporal sequence of monitoring. These elements also can be used to inform monitoring of the responses of other taxonomic groups to human activities.

Effects of Agmatine on Depressive-Like Behavior Induced by Intracerebroventricular Administration of 1-Methyl-4-phenylpyridinium (MPP+) - Morgana Moretti; Vivian Binder Neis; Filipe Carvalho Matheus; Mauricio Peña Cunha; Priscila Batista Rosa; Camille Mertins Ribeiro; Ana Lúcia S. Rodrigues; Rui Daniel Prediger (Neurotoxicity Research, 2015)

Ant community in natural fragments of the Brazilian wetland: species–area relation and isolation - Rafael G. Cuissi; Chaim J. Lasmar; Tamara S. Moretti; Fernando A. Schmidt; Wedson D. Fernandes; Andreia B. Falleiros; José H. Schoereder; Carla R. Ribas (Journal of Insect Conservation, 2015)

Model Space Exploration for Determining Landslide Source History from Long-Period Seismic Data - Juan Zhao; Laurent Moretti; Anne Mangeney; Eléonore Stutzmann; Hiroo Kanamori; Yann Capdeville; Eliza S. Calder; Clément Hibert; Patrick J. Smith; Paul Cole; Anne LeFriant (Pure and Applied Geophysics, 2015)

No evidence for leaf‐trait dissimilarity effects on litter decomposition, fungal decomposers, and nutrient dynamics - André Frainer; Marcelo S. Moretti; Wenjing Xu; Mark O. Gessner (Ecology, 2015)
Biodiversity and ecosystem‐functioning theory suggest that litter mixtures composed of dissimilar leaf species can enhance decomposition due to species trait complementarity. Here we created a continuous gradient of litter chemistry trait variability within species mixtures to assess effects of litter dissimilarity on three related processes in a natural stream: litter decomposition, fungal biomass accrual in the litter, and nitrogen and phosphorus immobilization. Litter from a pool of eight leaf species was analyzed for chemistry traits affecting decomposition (lignin, nitrogen, and phosphorus) and assembled in all of the 28 possible two‐species combinations. Litter dissimilarity was characterized in terms of a range of trait‐diversity measures, using Euclidean and Gower distances and dendrogram‐based indices. We found large differences in decomposition rates among leaf species, but no significant relationships between decomposition rate of individual leaf species and litter trait dissimilarity, irrespective of whether decomposition was mediated by microbes alone or by both microbes and litter‐consuming invertebrates. Likewise, no effects of trait dissimilarity emerged on either fungal biomass accrual or changes during decomposition of nitrogen or phosphorus concentrations in individual leaf species. In line with recent meta‐analyses, these results provide support for the contention that litter diversity effects on decomposition, at least in streams, are less pronounced than effects on terrestrial primary productivity.

Habitat connectivity shapes urban arthropod communities: the key role of green roofs - S. Braaker; J. Ghazoul; M. K. Obrist; M. Moretti (Ecology, 2014)
The installation of green roofs, defined here as rooftops with a shallow soil cover and extensive vegetation, has been proposed as a possible measure to mitigate the loss of green space caused by the steady growth of cities. However, the effectiveness of green roofs in supporting arthropod communities, and the extent to which they facilitate connectivity of these communities within the urban environment is currently largely unknown. We investigated the variation of species community composition (β diversity) of four arthropod groups with contrasting mobility (Carabidae, Araneae, Curculionidae, and Apidae) on 40 green roofs and 40 extensively managed green sites on the ground in the city of Zurich, Switzerland. With redundancy analysis and variation partitioning, we (1) disentangled the relative importance of local environmental conditions, the surrounding land cover composition, and habitat connectivity on species community composition, (2) searched for specific spatial scales of habitat connectivity for the different arthropod groups, and (3) discussed the ecological and functional value of green roofs in cities. Our study revealed that on green roofs community composition of high‐mobility arthropod groups (bees and weevils) were mainly shaped by habitat connectivity, while low‐mobility arthropod groups (carabids and spiders) were more influenced by local environmental conditions. A similar but less pronounced pattern was found for ground communities. The high importance of habitat connectivity in shaping high‐mobility species community composition indicates that these green roof communities are substantially connected by the frequent exchange of individuals among surrounding green roofs. On the other hand, low‐mobility species communities on green roofs are more likely connected to ground sites than to other green roofs. The integration of green roofs in urban spatial planning strategies has great potential to enable higher connectivity among green spaces, so that eventually even communities of low‐mobility species become connected. Furthermore, improving the design of green roofs (composition and configuration of vegetation and soil types) could enhance the ecological value, particularly for low‐mobility species.

Herbivore species identity mediates interspecific competition between plants - S. Ibanez; M. Bison; S. Lavorel; M. Moretti (Community Ecology, 2013)

Protective Effects of Ascorbic Acid on Behavior and Oxidative Status of Restraint-Stressed Mice - Morgana Moretti; Josiane Budni; Danubia Bonfanti dos Santos; Alessandra Antunes; Juliana Felipe Daufenbach; Luana Meller Manosso; Marcelo Farina; Ana Lúcia S. Rodrigues (Journal of Molecular Neuroscience, 2013)

High-Resolution Fibre-Optic Temperature Sensing: A New Tool to Study the Two-Dimensional Structure of Atmospheric Surface-Layer Flow - Christoph K. Thomas; Adam M. Kennedy; John S. Selker; Ayla Moretti; Martin H. Schroth; Alexander R. Smoot; Nicholas B. Tufillaro; Matthias J. Zeeman (Boundary-Layer Meteorology, 2012)

Global patterns of stream detritivore distribution: implications for biodiversity loss in changing climates - Luz Boyero; Richard G. Pearson; David Dudgeon; Verónica Ferreira; Manuel A. S. Graça; Mark O. Gessner; Andrew J. Boulton; Eric Chauvet; Catherine M. Yule; Ricardo J. Albariño; Alonso Ramírez; Julie E. Helson; et al. (Global Ecology and Biogeography, 2012)
Aim We tested the hypothesis that shredder detritivores, a key trophic guild in stream ecosystems, are more diverse at higher latitudes, which has important ecological implications in the face of potential biodiversity losses that are expected as a result of climate change. We also explored the dependence of local shredder diversity on the regional species pool across latitudes, and examined the influence of environmental factors on shredder diversity. Location World‐wide (156 sites from 17 regions located in all inhabited continents at latitudes ranging from 67° N to 41° S). Methods We used linear regression to examine the latitudinal variation in shredder diversity at different spatial scales: alpha (α), gamma (γ) and beta (β) diversity. We also explored the effect of γ‐diversity on α‐diversity across latitudes with regression analysis, and the possible influence of local environmental factors on shredder diversity with simple correlations. Results Alpha diversity increased with latitude, while γ‐ and β‐diversity showed no clear latitudinal pattern. Temperate sites showed a linear relationship between γ‐ and α‐diversity; in contrast, tropical sites showed evidence of local species saturation, which may explain why the latitudinal gradient in α‐diversity is not accompanied by a gradient in γ‐diversity. Alpha diversity was related to several local habitat characteristics, but γ‐ and β‐diversity were not related to any of the environmental factors measured. Main conclusions Our results indicate that global patterns of shredder diversity are complex and depend on spatial scale. However, we can draw several conclusions that have important ecological implications. Alpha diversity is limited at tropical sites by local factors, implying a higher risk of loss of key species or the whole shredder guild (the latter implying the loss of trophic diversity). Even if regional species pools are not particularly species poor in the tropics, colonization from adjacent sites may be limited. Moreover, many shredder species belong to cool‐adapted taxa that may be close to their thermal maxima in the tropics, which makes them more vulnerable to climate warming. Our results suggest that tropical streams require specific scientific attention and conservation efforts to prevent loss of shredder biodiversity and serious alteration of ecosystem processes.

Controlling a vancomycin-resistant enterococci outbreak in a Brazilian teaching hospital - M. L. Moretti; L. G. Oliveira Cardoso; C. E. Levy; A. Nowakosky; L. F. Bachur; O. Bratfich; M. L. Leichsenring; R. Fagnani; S. M. Peres Evangelista Dantas; M. R. Resende; P. Trabasso (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

What is more important for invertebrate colonization in a stream with low-quality litter inputs: exposure time or leaf species? - Raphael Ligeiro; Marcelo S. Moretti; José Francisco Gonçalves; Marcos Callisto (Hydrobiologia, 2010)

Identification, mycotoxin risk and pathogenicity of Fusarium species associated with fig endosepsis in Apulia, Italy - A. Moretti; L. Ferracane; S. Somma; V. Ricci; G. Mulè; A. Susca; A. Ritieni; A.F. Logrieco (Food Additives & Contaminants: Part A, 2010)

Trichothecene and beauvericin mycotoxin production and genetic variability in Fusarium poae isolated from wheat kernels from northern Italy - S. Somma; C. Alvarez; V. Ricci; L. Ferracane; A. Ritieni; A. Logrieco; A. Moretti (Food Additives & Contaminants: Part A, 2010)

Sighting characteristics and photo-identification of Cuvier’s beaked whales (Ziphius cavirostris) near San Clemente Island, California: a key area for beaked whales and the military? - Erin A. Falcone; Gregory S. Schorr; Annie B. Douglas; John Calambokidis; Elizabeth Henderson; Megan F. McKenna; John Hildebrand; David Moretti (Marine Biology, 2009)

Leaf abundance and phenolic concentrations codetermine the selection of case-building materials by Phylloicus sp. (Trichoptera, Calamoceratidae) - Marcelo S. Moretti; Rafael D. Loyola; Bárbara Becker; Marcos Callisto (Hydrobiologia, 2009)

Lipid-lowering drug use in Italian primary care: effects of reimbursement criteria revision - G. Trifirò; M. Alacqua; S. Corrao; S. Moretti; D. U. Tari; M. Galdo; A. P. Caputi; V. Arcoraci (European Journal of Clinical Pharmacology, 2008)

Viral outcome of simian–human immunodeficiency virus SHIV-89.6P adapted to cynomolgus monkeys - A. Borsetti; S. Baroncelli; M. T. Maggiorella; S. Bellino; S. Moretti; L. Sernicola; R. Belli; B. Ridolfi; S. Farcomeni; D. R. M. Negri; A. Cafaro; B. Ensoli; et al. (Archives of Virology, 2008)

Importance of species abundance for assessment of trait composition: an example based on pollinator communities - F. Bello; J. Lepš; S. Lavorel; M. Moretti (Community Ecology, 2007)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Pathogenicity and mycotoxin production by Fusarium proliferatum isolated from onion and garlic in Serbia - S. Stankovic; J. Levic; T. Petrovic; A. Logrieco; A. Moretti (European Journal of Plant Pathology, 2007)

Use and safety profile of antiepileptic drugs in Italy - M. L. Iorio; U. Moretti; S. Colcera; L. Magro; I. Meneghelli; D. Motola; A. L. Rivolta; F. Salvo; G. P. Velo (European Journal of Clinical Pharmacology, 2007)

Diagnosis of candidemia by polymerase chain reaction and blood culture: prospective study in a high-risk population and identification of variables associated with development of candidemia - M. S. Moreira-Oliveira; Y. Mikami; M. Miyaji; T. Imai; A. Z. Schreiber; M. L. Moretti (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Mainshocks and aftershocks of the 2002 molise seismic sequence, southern Italy - C. Chiarabba; P. De Gori; L. Chiaraluce; P. Bordoni; M. Cattaneo; M. De Martin; A. Frepoli; A. Michelini; A. Monachesi; M. Moretti; G. P. Augliera; E. D'Alema; et al. (Journal of Seismology, 2005)

Potential role of SEN virus on liver enzyme abnormalities in patients positive for hepatitis C virus with or without HIV infection - E. Quiros-Roldan; F. Moretti; C. Torti; V. Tirelli; R. Stellini; S. Pirovano; G. Carosi; L. Imberti (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Comparative analysis of early embryonic sunflower cDNA libraries - Ccile Ben; Tarek Hewezi; Marie Franoise Jardinaud; Frdrique Bena; Nathalie Ladouce; Sbastien Moretti; Cecilia Tamborindeguy; Thierry Liboz; Michel Petitprez; Laurent Gentzbittel (Plant Molecular Biology, 2005)

Relationship between the incidences of ear and spikelet infection of Fusarium ear blight in wheat - X.-m. Xu; D.W. Parry; S.G. Edwards; B.M. Cooke; F.M. Doohan; A. Maanen; J.M. Brennan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; L. Hornok; et al. (European Journal of Plant Pathology, 2004)

Molecular phylogenetics of Dipsacaceae reveals parallel trends in seed dispersal syndromes - P. Caputo; S. Cozzolino; A. Moretti (Plant Systematics and Evolution, 2004)

Recessive resistance genes against potyviruses are localized in colinear genomic regions of the tomato (Lycopersicon spp.) and pepper (Capsicum spp.) genomes - G. Parrella; S. Ruffel; A. Moretti; C. Morel; A. Palloix; C. Caranta (Theoretical and Applied Genetics, 2002)

Effect of Fusarium, Paecilomyces and Trichoderma formulations against aphid Schizaphis graminum - S. Ganassi; A. Moretti; C. Stornelli; B. Fratello; A.M. Bonvicini Pagliai; A. Logrieco; M.A. Sabatini (Mycopathologia, 2001)

Applicability of Aspecific Noninvasive Methods for Biomonitoring of Occupational Exposure to Deltamethrin: Preliminary Study Using an Animal Model - M. Moretti; M. Villarini; G. Scassellati-Sforzolini; R. Pasquini; S. Monarca (Archives of Environmental Contamination and Toxicology, 1997)

Fusarium Proliferatum from Asparagus, in Italy: Occurrence, Fertility and Toxigenicity - A. Moretti; A. Logrieco; B. Doko; S. Frisullo; A. Visconti; A. Bottalico (Cereal Research Communications, 1997)

Chelation therapy and the tissue distribution and excretion of lead in mice - Elsie M. B. Sorensen; Elizabeth S. Moretti; Arthur Lindenbaum (Archives of Environmental Contamination and Toxicology, 1980)